(untitled) (Research, Society and Development, 2022)
Cardiovascular diseases are the main cause of death in the world and despite advances in treatment and prevention today, cardiorespiratory arrest is a major global public health problem. Adequate care for cardiorespiratory arrest requires organization, quick, assertive decision and skills on the part of those involved in the care, so it is essential that professionals maintain constant training and methods of reassessing their skills. The objective of this study was to analyze the effectiveness of external chest compressions performed by firefighters, with an execution time of two minutes, in training during the Covid-19 pandemic. This is a descriptive, correlational study, carried out from January to November 2020, at the Ribeirão Preto Fire Department, with adult participants, military firefighters, belonging to a specific group, comprising a sample of 44 volunteers. The study addressed the invitation to participants and their characterization as well as a pre-test to analyze the effectiveness of external chest compressions for two minutes, after which there was a lecture of approximately fifteen minutes on cardiopulmonary resuscitation and skills training for external chest compressions. After training, there was a test of the effectiveness of external chest compressions for two minutes. For statistical analysis, a Bayesian approach was used to provide probabilistic statements. Through the methodological tools for analyzing the effectiveness of chest compressions, high scientific accuracy was observed and the results identified an excellent performance of the firefighters, both in the pre-test and in the post-test, in addition to a moderate perception of effort in compressions.